Recovery of Banksia and Hakea Communities after Fire in Mediterranean Australia -- The Role of Species Identity and Functional Attributes - Lamont, Byron; Groom, Philip; Richards, M.; Witkowski, E. (1999)
Up to thirteen demographic, four morphological and four ecophysiological attributes were assessed in each of three studies of postfire recruitment patterns in mediterranean southwestern Australia. Three to seven of the most prominent, congeneric shrub species in each of five communities were monitored following a total of six fires, and numbers of individuals prefire were compared with those over two to four winters postfire. The proportion of individuals in each species only sometimes reflected the proportion at an earlier time. At least one species differed from the rest for twenty-six of a total of twenty- seven demographic steps assessed. Initial seedlings/ parent, which was largely a function of seeds available, and, to a lesser extent, level of germination, were the most important attributes in accounting for the recruitment patterns. There was a trend for the faster growing, drought avoiding species to increase at the expense of the others. In the most comprehensive study, life form (four nonsprouting Hcikea spp. i. four resprouting Hcakea spp.) was the best predictor of the recovery pattern. This was through its association with seed availability and level of germination and, to a lesser extent, drought survival (all higher for nonsprouters). Leaf type, as an indicator of drought tolerance, had inconsistent predictive power between studies. The least summer stressed species, in terms of survival and water relations, tended to have the largest seedlings derived from the largest seeds, but there were notable exceptions. Within each life form category, species behaviour varied widely, making most predictions of postfire community dynamics based on relative prefire numbers little more than conjectural. However, in only one of the three studies were the trends sufficiently clear to show that postfire densities would never mirror those prefire.